2020
DOI: 10.1007/s42452-020-3104-6
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and time resolved determination of the vibrational temperature in ignition sparks by variation of the dwell time

Abstract: The ignition process initiates the combustion in spark-ignition engines. Therefore, understanding the ignition process is an important aspect in developing more efficient combustion engines. In this thesis, the vibrational temperature of an ignition spark in air under atmospheric pressure and room temperature is observed in spatial and temporal resolution. The temperature is determined by comparing simulated spectra with the measured spectra of the second positive system of N 2 between 360 and 381 nm. Changing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…The position of the measurement within the plasma was not specified and the result is for a short, pulsed plasma. Michler [11,12] reported temperature values for a sparkplug geometry of a pulsed plasma for glow and arc discharge with spatial dimensions. The results showed that the rotational temperature increased near the anode but was also significantly higher near the cathode.…”
Section: Introductionmentioning
confidence: 99%
“…The position of the measurement within the plasma was not specified and the result is for a short, pulsed plasma. Michler [11,12] reported temperature values for a sparkplug geometry of a pulsed plasma for glow and arc discharge with spatial dimensions. The results showed that the rotational temperature increased near the anode but was also significantly higher near the cathode.…”
Section: Introductionmentioning
confidence: 99%